Estimating Regionalized Hydrological Impacts of Climate Change Over Europe by Performance-Based Weighting of CORDEX Projections - Sperna Weiland, Frederiek C.; Visser, Robrecht D.; Greve, Peter; Bisselink, Berny; Brunner, Lukas; Weerts, Albrecht H. (Frontiers in Water, 2021)
Ensemble projections of future changes in discharge over Europe show large variation. Several methods for performance-based weighting exist that have the potential to increase the robustness of the change signal. Here we use future projections of an ensemble of three hydrological models forced with climate datasets from EURO-CORDEX. The experiment is set-up for nine river basins spread over Europe that hold different climate and catchment characteristics. We evaluate the ensemble consistency and apply two weighting approaches; the Climate model Weighting by Independence and Performance (ClimWIP) that focuses on meteorological variables and the Reliability Ensemble Averaging (REA) in our study applied to discharge statistics per basin. For basins with a strong climate signal in Southern and Northern Europe the consistency in the set of projections is large. For rivers in Central Europe the differences between models become more pronounced. Both weighting approaches assign high weights to single GCMs. The ClimWIP method results in ensemble mean weighted changes that differ only slightly from the non-weighted mean. The REA method influences the weighted mean more, yet here the signal is dominated by one or two GCMs with a small bias for the historical climate that can provide deviating projections for the future. It is not apparent that the GCM signal dominates the overall change signal, i.e. there is no strong intra GCM consistency. This may have reduced the influence of the weighing methods.